Tissue Culture of Bambusa Nutans Wall ex Munro and Dendrocalamus Asper (Schult. & Schult.f.) Backer ex Heyne: Optimizing Protocol for Commercial Exploitation - Choudhary, A. K.; Kumari, Swati; Kumar, Anand; Kumari, Priyanka; Kumar, Rohit; Khan, Imran; Ranjan, Rajiv (European Journal of Applied Sciences, 2025)
Bamboo is a fast growing, highly versatile bioresource plant that significantly contributes to both industrial applications and ecological balance. The present study focuses on optimizing tissue culture protocols for commercial exploitation of two economically important bamboo species Bambusa nutans Wall ex Munro and Dendrocalamus asper (Schult. & Schult.f.) Backer ex Heyne. We employed nodal segments as explants, which were surface sterilized and grown in Murashige and Skoog (MS) medium enriched with different plant growth regulators (alone or in various combinations). Seasonal variations in bud initiation and proliferations were monitored. The experiments were conducted in triplicate using a completely randomized design with 10 replicates each and significance levels were determined through Analysis of variance (ANOVA), with mean comparison performed using Duncan’s Multiple Range Test (DMRT) at p≤0.05. The rate of bud initiation was observed during mid spring to summer. The maximum number of shoots (4.80 ± 0.28 in B. nutans and 5.04 ± 0.05 in D. asper) were achieved in MS medium containing 5.0 mg/l BAP, however, the shoot length was significantly high in 2.5mg/l of BAP. Liquid media promoted better shoot growth and quality. NAA and additives had positive influence on shoot multiplication in both the species. For root formation in both species, NAA (0.5 mg/l) in half strength of basal medium was the most effective among all the auxins.